9(f+3)=45

Simple and best practice solution for 9(f+3)=45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(f+3)=45 equation:



9(f+3)=45
We move all terms to the left:
9(f+3)-(45)=0
We multiply parentheses
9f+27-45=0
We add all the numbers together, and all the variables
9f-18=0
We move all terms containing f to the left, all other terms to the right
9f=18
f=18/9
f=2

See similar equations:

| −4/5w=−28 | | 6x-24=1 | | 68=24+4d | | -8a=-152 | | 12(x+9)=-108. | | 15=4k-13 | | 2x^2+5x=260 | | -3(5x+7)=-51 | | -2(3x-1)=140 | | (10x(1+2x)=) | | 8x+6=4x+48 | | (2x+5)(x)=260 | | 32x-16=6x+18 | | 1/3z=-5/6+1/6z | | -5=-14z | | 2.6+13.3x=3.8x-(-1-9.7x) | | 56=8+3(y+4 | | 3x+2x=43-8 | | X-1/4-x+1/10=1 | | -7x+9=-x+27 | | 8y+2=4y-34 | | -2-13.8x=-14x+1 | | 10x-8=-2 | | -Y=2/3x+4 | | 8-4.50x=57.50 | | 11+t=26 | | -3(v-+4)=2v-37 | | 6x-4x=15 | | 4^2+8x+3=0 | | 6n^2=-n+40 | | -10+m=-32 | | 85-x=94-2x |

Equations solver categories